Traditional Institutions and Good Governance in Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2023)
Traditional institutions as custodian of cultures and traditions have continued to play a very significant role before and during colonial independence of many African societies. In Nigeria they provide a system of administration with an utmost aim of maintaining a stable governance through tradition, customs, and law and order. But with the advent of democracy, the role of traditional institutions became less recognized in the democratic system of government. The paper examined the role and relevance of indigenous traditional institutions to good governance. The paper was a quantitative research. Data was obtained from secondary sources including journals, articles and publications. The paper revealed that traditional institutions play a very significant role of sustaining culture and traditions, informally managing of conflict, maintaining peace, custodian of oral traditional history of the people etc. before and during colonial era. But with the advent of democracy, their power and duties became less recognized in the democratic system of government because traditional institutions were negated to the back door and politicized. Functionalism theory of Emile Durkheim (1858 – 1917) was employed to explain how society is an integrated whole, where all parts are interconnected and traditional institutions as part of the society, play a vital function of maintaining stability and contributing to the wellbeing of its members in terms of law, order and governance. The paper concluded that if the goal of government at all levels is to provide good governance to the people, rapid in social wealth and economic development, traditional institutions need to be integrated and assigned greater responsibilities in Nigerian’s contemporary democratic system of government because they have the ability to promote grassroots governance and facilitate access of rural communities to public services.